2014
DOI: 10.1002/2013pa002579
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene primary productivity and sea surface temperature variations in the northeastern Arabian Sea: Implications for winter monsoon variability

Abstract: Variability in the oceanic environment of the Arabian Sea region is strongly influenced by the seasonal monsoon cycle of alternating wind directions. Prominent and well studied is the summer monsoon, but much less is known about late Holocene changes in winter monsoon strength with winds from the northeast that drive convective mixing and high surface ocean productivity in the northeastern Arabian Sea. To establish a high-resolution record of winter monsoon variability for the late Holocene, we analyzed alkeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 96 publications
(180 reference statements)
2
54
1
Order By: Relevance
“…TEX 86 -and alkenone-based SST reconstructions of cores NIOP905 and SO42-KL74 were shown to differ in magnitude and phase as TEX 86 temperature reconstructions seem to have a SW monsoon bias (Huguet et al, 2006). Munz et al (2015) showed that winter temper-atures derived from planktic foraminiferal assemblages had stronger amplitudes than the alkenone-based annual average SST reconstructions in SO130-275KL of Böll et al (2014). Two of the records used in this study have both, alkenone and Mg / Ca temperature.…”
Section: Integration and Averaging Of Sst And δ 15 N Reconstructionsmentioning
confidence: 72%
See 2 more Smart Citations
“…TEX 86 -and alkenone-based SST reconstructions of cores NIOP905 and SO42-KL74 were shown to differ in magnitude and phase as TEX 86 temperature reconstructions seem to have a SW monsoon bias (Huguet et al, 2006). Munz et al (2015) showed that winter temper-atures derived from planktic foraminiferal assemblages had stronger amplitudes than the alkenone-based annual average SST reconstructions in SO130-275KL of Böll et al (2014). Two of the records used in this study have both, alkenone and Mg / Ca temperature.…”
Section: Integration and Averaging Of Sst And δ 15 N Reconstructionsmentioning
confidence: 72%
“…solation during the glacial (Böll et al, 2014(Böll et al, , 2015Reichart et al, 2004). The observed regional differences in temperature rise from the LGM to the Holocene (Fig.…”
Section: Temperature Differences Between Glacial and The Holocenementioning
confidence: 87%
See 1 more Smart Citation
“…In order to calculate SST variations over the last 2000 years from foraminiferal transfer functions, we studied samples from the uppermost 15 cm of Sonne 90 box-core 39KG (von Rad et al, 1995(von Rad et al, , 1999 and the uppermost 167 cm of Sonne 130 piston-core 275KL (Böll et al, 2014;von Rad et al, 1998). Both cores were taken at the same station from the continental margin off Pakistan (Figure 1; 24°50′N, 65°55′E, 695 m water depth), allowing us to achieve a continuous record over the last 2000 years.…”
Section: Late Holocene Sediment Record From the Pakistan Marginmentioning
confidence: 99%
“…This suggests, verified by satellite-derived concentrations of monthly chlorophyll a in the surface waters (Feldman and McClain, 2013), that the annual cycle of sea surface properties in this area is dominated by winter conditions. In a previous paper (Böll et al, 2014), we attempted to reconstruct winter monsoon intensity from regionally calibrated alkenone temperatures and stable nitrogen isotopes in laminated sediment cores (39KG/275KL) from the Pakistan margin ( Figure 1). There, we identified a general cooling trend of reconstructed annual mean temperatures (AM-SST) over the last 2400 years together with several periods of century-scale temperature changes that occurred largely in phase with geochemical productivity estimates.…”
Section: Introductionmentioning
confidence: 99%